Technology simulation training in the production of drug tablets for pharmaceutical vocational school students in Bekasi City - Anindita, Reza; Beandrade, Maya Uzia; Putri, Intan Kurnia; Nathalia, Dede Dwi; Perwitasari, Melania (Journal of Community Service and Empowerment, 2023)
One of the most dominant types of preparations used by the public is tablets. This community service and empowerment (CSE) aims to introduce and provide training on making tablets with innovative tablet printing machine technology in the pharmaceutical industry and to build partners with SMKs to provide access to education for the vocational level by science and technology while at the same time offering a scholarship program as access to continuing higher education at STIKes Mitra Keluarga for high achieving and financially disadvantaged students. This CSE method includes planning carried out by making an offer to the Pharmacy Vocational School in Bekasi City and making activity flyers to be distributed for class 12, 10, and 11. The implementation was carried out by giving pre-tests, materials, and simulation practices for making drugs with tablet printing machines at STIKES Mitra Keluarga. The evaluation stage is carried out by giving post-test questions. Data analysis in this study was carried out using descriptive and comparative tests using paired t-tests. The results of this CSE show that the value of knowledge and understanding of 35 students before being given material treatment and training was 57 and after being given treatment it was 94 with a percentage increase of 43%. Therefore, this CSE activities is able to increase the knowledge and understanding of 35 class X, XI and XII students of the Bakti Kartini Pharmacy Vocational School regarding making medicine using a tablet printing machine in a real way.